2017
DOI: 10.1021/acs.jpcb.7b06930
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Aromatic Isomers in Acetone: An Investigation on the Effects of Intramolecular and Intermolecular Hydrogen Bonding

Abstract: Limiting mutual diffusivities of o- and m-isomers of methylaniline, nitroaniline, nitrophenol, and aminophenol were measured in acetone at 298.2 K by the Taylor dispersion method. The data reveal that all of the o-substituted solutes capable of intramolecular hydrogen bonding diffuse faster than their m-counterparts without such bonding. By taking into account of the small corrections for the differences in molecular shape and steric hindrance between the o- and m-isomers that can form solute-solvent complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…The limiting mutual diffusivities of the basically nonpolar aromatic compounds ( D 12 N ) in acetone, together with their precisions, are presented in Table for the temperature range from 268.15 to 328.15 K. All of the reported data were measured in this work by the Taylor dispersion technique, except those at 298.15 K that were mainly collected from previous studies. ,,, Also given in the table are the van der Waals volumes ( V 1 ) of the solute molecules, which were obtained by the method of group increments. ,,, Note that the 10 aromatic solutes listed in Table are all disc-shaped hydrocarbons that are incapable of H-bonding with acetone, as they do not have any proton-donating (H-donating) groups. For solutes that are similar in shape, many investigations ,,,,, have shown that a linear relationship exists between the reciprocal of D 12 N and V 1 at constant temperature, i.e., where a and b are constants for a given temperature. It is noteworthy that eq actually originates from the rough-hard-sphere theory with simplification for the diffusion of nonassociated solutes of the same shape in a given solvent at constant temperature. , This equation is generally applicable for a fairly wide range of solute sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The limiting mutual diffusivities of the basically nonpolar aromatic compounds ( D 12 N ) in acetone, together with their precisions, are presented in Table for the temperature range from 268.15 to 328.15 K. All of the reported data were measured in this work by the Taylor dispersion technique, except those at 298.15 K that were mainly collected from previous studies. ,,, Also given in the table are the van der Waals volumes ( V 1 ) of the solute molecules, which were obtained by the method of group increments. ,,, Note that the 10 aromatic solutes listed in Table are all disc-shaped hydrocarbons that are incapable of H-bonding with acetone, as they do not have any proton-donating (H-donating) groups. For solutes that are similar in shape, many investigations ,,,,, have shown that a linear relationship exists between the reciprocal of D 12 N and V 1 at constant temperature, i.e., where a and b are constants for a given temperature. It is noteworthy that eq actually originates from the rough-hard-sphere theory with simplification for the diffusion of nonassociated solutes of the same shape in a given solvent at constant temperature. , This equation is generally applicable for a fairly wide range of solute sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews of the fundamental principles of the Taylor dispersion technique have been given by Cussler and by Tyrrell and Harris . The experimental setup and procedure in this work were basically the same as those reported earlier in our previous studies. Actually, the equipment and instruments resembled those constituting a common HPLC (high-performance liquid chromatography) system, i.e., a solvent delivery pump, a sample injector, a column, and a detector. Instead of an HPLC column, however, a diffusion tube of length 91.4 m was used for the diffusivity measurements in this work.…”
Section: Experimental Sectionmentioning
confidence: 97%
See 2 more Smart Citations
“…Phenomena of mass transport by diffusion are ubiquitous in chemical and biological science and engineering. , Among them, molecular diffusion in hydrogen-bonding associated system has always been recognized as a challenging problem. , However, few studies have been reported to learn molecular diffusion in nanoscale. Combining the advantages of our Al 2 O 3 -based 3D sensing platform, we have conducted a real-time observation for the acetone molecular diffusion in DI water in nanospace.…”
Section: Results and Discussionmentioning
confidence: 99%